Hyperpersonal feedback and online romance fraud: an empirical examination - Wang, Fangzhou (Journal of crime and justice, 2025)
Online romance fraud occurs when an offender uses deception to present a fake online identity to gain a victim’s affection and trust and then defrauds the victim in some way. Despite the crime’s serious impact, there is a lack of empirical knowledge regarding the processes by which it is carried out. Specifically, little is known about how the reciprocal interaction – or feedback – between online romance fraudsters and victims facilitates the crime. This study addresses this gap by using a randomized experimental design to explore how variations in potential reward presented by a fictional victim influence the strategies of fraudsters. To guide our examination, we draw from the hyperpersonal model of communication. Our analysis of sequential email exchanges with 94 online romance fraudsters reveals that their self-selective strategies are shaped by a feedback process between their messages and the victim’s impressions. We discuss implications for online romance fraud and the hyperpersonal model of communication.